2005
DOI: 10.1086/468188
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Synapsis Proceeds from a Limited Number of Subtelomeric Sites in the Human Male

Abstract: The formation of the synaptonemal complex (SC) is a crucial early step in the meiotic process, but relatively little is known about the establishment of the human SC. Accordingly, we recently initiated a study of synapsis in the human male, combining immunofluorescence and fluorescence in situ hybridization methodologies to analyze prophase spermatocytes from a series of control individuals. Our results indicate that synapsis is a tightly regulated process, with relatively little variation among individuals. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 35 publications
7
62
0
Order By: Relevance
“…1 However, in mammals this may not be the case, since cytological observations have indicated that synapsis proceeds from the telomeric ends of the paired homologous chromosomes in humans. 2 Telomeres function during the initial phase of chromosome pairing in both yeast and mammals. During this phase, all telomeres cluster on the nuclear membrane, while the chromosomal arms loop towards the center of the nucleus, forming the transient bouquet stage.…”
Section: Induction and Repair Of Meiotic Dsbsmentioning
confidence: 99%
“…1 However, in mammals this may not be the case, since cytological observations have indicated that synapsis proceeds from the telomeric ends of the paired homologous chromosomes in humans. 2 Telomeres function during the initial phase of chromosome pairing in both yeast and mammals. During this phase, all telomeres cluster on the nuclear membrane, while the chromosomal arms loop towards the center of the nucleus, forming the transient bouquet stage.…”
Section: Induction and Repair Of Meiotic Dsbsmentioning
confidence: 99%
“…Several arguments have led to the proposition that SIC are located at the same sites where crossovers will form (Henderson & Keeney 2005). In humans, analysis of synapsis initiation has indeed suggested a limited number of sites preferentially located near sub-telomeric regions in correlation with CO density (Brown et al 2005).…”
Section: Properties Of Nco Productsmentioning
confidence: 99%
“…Furthermore it has been seen that the centromere avoids spreading the synapsis from q-arm to p-arm and vice versa (Brown et al, 2005). Fig.…”
Section: Synapsismentioning
confidence: 95%
“…Several studies of human chromosomes have shown that at least one crossover occurs in each arm, except in short arms of acrocentric chromosomes, where crossovers occur infrequently. Further, the existence of a crossover inhibits the formation of another in a nearby region, a phenomenon known as "interference" (Brown et al, 2005; reviewed by Lynn et al, 2004;Sun et al, 2004a).…”
Section: Recombinationmentioning
confidence: 99%